Tissue Inhibitor of Metalloproteinase-3 Ameliorates Diabetes-Induced Retinal Inflammation - Abu El-Asrar, Ahmed M.; Ahmad, Ajmal; Nawaz, Mohd Imtiaz; Siddiquei, Mohammad Mairaj; De Zutter, Alexandra; Vanbrabant, Lotte; Gikandi, Priscilla W.; Opdenakker, Ghislain; Struyf, Sofie (Frontiers in Physiology, 2022)
Purpose: Endogenous tissue inhibitor of matrix metalloproteinase-3 (TIMP-3) has powerful regulatory effects on inflammation and angiogenesis. In this study, we investigated the role of TIMP-3 in regulating inflammation in the diabetic retina. Methods: Vitreous samples from patients with proliferative diabetic retinopathy (PDR) and nondiabetic patients were subjected to Western blot analysis. Streptozotocin-treated rats were used as a preclinical diabetic retinopathy (DR) model. Blood-retinal barrier (BRB) breakdown was assessed with fluorescein isothiocyanate-conjugated dextran. Rat retinas, human retinal microvascular endothelial cells (HRMECs) and human retinal Müller glial cells were studied by Western blot analysis and ELISA. Adherence of human monocytes to HRMECs was assessed and in vitro angiogenesis assays were performed. Results: TIMP-3 in vitreous samples was largely glycosylated. Intravitreal injection of TIMP-3 attenuated diabetes-induced BRB breakdown. This effect was associated with downregulation of diabetes-induced upregulation of the p65 subunit of NF-B, intercellular adhesion molecule-1 (ICAM-1) and vascular endothelial growth factor (VEGF), whereas phospho-ERK1/2 levels were not altered. In Müller cell cultures, TIMP-3 significantly attenuated VEGF upregulation induced by high-glucose (HG), the hypoxia mimetic agent cobalt chloride (CoCl2) and TNF- and attenuated MCP-1 upregulation induced by CoCl2 and TNF-, but not by HG. TIMP-3 attenuated HG-induced upregulation of phospho-ERK1/2, caspase-3 and the mature form of ADAM17, but not the levels of the p65 subunit of NF-B and the proform of ADAM17 in Müller cells. TIMP-3 significantly downregulated TNF--induced upregulation of ICAM-1 and VCAM-1 in HRMECs. Accordingly, TIMP-3 significantly decreased spontaneous and TNF-- and VEGF-induced adherence of monocytes to HRMECs. Finally, TIMP-3 significantly attenuated VEGF-induced migration, chemotaxis and proliferation of HRMECs. Conclusion: In vitro and in vivo data point to anti-inflammatory and anti-angiogenic effects of TIMP-3 and support further studies for its applications in the treatment of diabetic retinopathy.